1984
DOI: 10.1002/asna.2113050403
|View full text |Cite
|
Sign up to set email alerts
|

On the Structure of the Coma Cluster of Galaxies

Abstract: The investigation of the distributions of number densities and radial velocities in the Coma cluster led us to the conclusion that this cluster possesses substructures. This result is in agreement with corresponding results for the Hydra I cluster and the Perseus cluster and with former conclusions by different authors that substructures are a typical phenomenon for a high percentage of all clusters of galaxies.Die Untersuchung der Anzahl-Dichte-Verteilung sowie der Verteilung der Radialgeschwindigkeiten im Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…It is believed that Coma has recently undergone a cluster-subcluster merger (Burns et al 1994b). This has been confirmed by several optical studies (Baier 1984;Fitchett & Webster 1987;Mellier et al 1988;Caldwell et al 1993;Zabludoff, Franx, & Geller 1993;Colless & Dunn 1996); however, the optical state of this cluster is still poorly understood (e. g. Geller & Beers 1982;Dressler & Schectman 1988;West & Bothun 1990). The merger hypothesis is supported by filamentary X-ray emission in the E and SE detected through a wavelet analysis (Vikhlinin, Forman & Jones 1997), and smaller X-ray subclumps detected by the Einstein IPC (Davis & Mushotzky 1993).…”
Section: O N C L U S I O N Ssupporting
confidence: 52%
See 1 more Smart Citation
“…It is believed that Coma has recently undergone a cluster-subcluster merger (Burns et al 1994b). This has been confirmed by several optical studies (Baier 1984;Fitchett & Webster 1987;Mellier et al 1988;Caldwell et al 1993;Zabludoff, Franx, & Geller 1993;Colless & Dunn 1996); however, the optical state of this cluster is still poorly understood (e. g. Geller & Beers 1982;Dressler & Schectman 1988;West & Bothun 1990). The merger hypothesis is supported by filamentary X-ray emission in the E and SE detected through a wavelet analysis (Vikhlinin, Forman & Jones 1997), and smaller X-ray subclumps detected by the Einstein IPC (Davis & Mushotzky 1993).…”
Section: O N C L U S I O N Ssupporting
confidence: 52%
“…Caldwell et al (1993) detected a number of 'EþA' (Dressler & Gunn 1983) galaxies, which are almost exclusively located to the SW of the cluster centre. This is a surprising result, since most of these post-starburst galaxies are detected in distant (z ϳ 0:2) clusters (Butcher & Oemler 1978, 1984Dressler & Gunn 1983;Couch & Sharples 1987). Abell 1795: Fig.…”
Section: A P P E N D I X a : I N D I V I D Ua L S O U R C E Smentioning
confidence: 94%
“…It is believed that Coma has recently undergone a cluster-subcluster merger (Burns et al 1994b). This has been confirmed by several optical studies (Baier 1984;Fitchett & Webster 1987;Mellier et al 1988;Caldwell et al 1993;Zabludoff, Franx, & Geller 1993;Colless & Dunn 1996); however, the optical state of this cluster is still poorly understood (e. g. Geller & Beers 1982;Dressler & Schectman 1988;West & Bothun 1990). The merger hypothesis is supported by filamentary X-ray emission in the E and SE detected through a wavelet analysis (Vikhlinin, Forman & Jones 1997), and smaller X-ray subclumps detected by the Einstein IPC (Davis & Mushotzky 1993).…”
Section: O N C L U S I O N Smentioning
confidence: 53%
“…Caldwell et al (1993) detected a number of 'EþA' (Dressler & Gunn 1983) galaxies, which are almost exclusively located to the SW of the cluster centre. This is a surprising result, since most of these post-starburst galaxies are detected in distant (z ϳ 0:2) clusters (Butcher & Oemler 1978, 1984Dressler & Gunn 1983;Couch & Sharples 1987). Abell 1795: Fig.…”
Section: A P P E N D I X a : I N D I V I D Ua L S O U R C E Smentioning
confidence: 99%
“…The present study extends the photometry of BLE92a to a complete galaxy sample covering approximately four times the area (still centred on the core), and reaches to fainter limiting magnitudes. The extra coverage and depth will enable us to obtain colours for the abnormal spectrum ‘’ galaxies of Caldwell et al (1993; 1996), many of which are to be found in the south‐west corner of the cluster around a group of galaxies dynamically associated with NGC 4839 (Baier 1984; Escalera, Slezak & Mazure 1992; Colless & Dunn 1996). Significant advances in detector technology since the work of BLE92a allow us to use much larger CCDs with greater U ‐band sensitivity.…”
Section: Introductionmentioning
confidence: 99%